Planar-bilayer activities of linear oligoester bolaamphiphiles - Chui, Jonathan K. W.; Fyles, Thomas M.; Luong, Horace (Beilstein Journal of Organic Chemistry, 2011)
Voltage-clamp experiments of eight oligoester bolaamphiphiles in two subclasses are described. Syntheses of three new terephthalate-based compounds were achieved in three linear steps. Together with five previously described, related compounds, the ion transport activity was assessed by means of the voltage-clamp technique. All of the compounds show multiple types of conductance behavior in planar bilayers, a subset of which was exponentially voltage-dependent. The varied and irregular activities were summarized with the aid of a recently developed “activity-grid” method.
Keywords: activity grid; single-molecule studies; synthetic ion channels; voltage clamp experiment